Some Aspects of the Analysis and Evaluation of Fixed Tangible Assets with Ecological Use - Ivanova, Rositsa (Research Papers, 2018)
This publication studies the fixed tangible assets with ecological use, and its subject matter covers some aspects of the methodology for their analysis.This publication is aimed at presenting a methodology for analysis of fixed tangible assets with ecological use. The following tasks are solved for achieving this aim: the methodological stages of the analysis are defined, a system of indicators is established, and methods for analysis and evaluation of fixed tangible assets with ecological use are proposed.As a result of the study, this publication suggests a methodology for analysis of fixed tangible assets with ecological use, which is theoretically justified and practically feasible in the business practice. Based on the obtained analytical information, the enterprise’s management may make proper and reasonable decisions for management of fixed tangible assets of ecological use.